Peningkatan Keterampilan Menulis Artikel Jurnal Pada Mahasiswa Sekolah Tinggi Ilmu Kesehatan Merangin Melalui Pelatihan Karya Tulis Ilmiah - Isra Miharti; Sahara; Anwar Sanusi; Febbry Romundza (Yayasan Darussalam Bengkulu, 2025)
A scientific journal is an academic publication containing articles or scientific studies, used to disseminate new discoveries, theories, and research findings in various fields of science. To produce scientific articles, students must be able to write; writing itself is a crucial skill in conveying ideas and concepts into written form. The purpose of this community service activity was to assist students who find it difficult to write scientific articles and how to publish them. This community service activity was carried out at the Merangin College of Health Sciences and was attended by 50 students from the midwifery and public health study programs. The implementation method in this service activity was carried out using lectures and question-and-answer discussions. The results of the activity, students began to understand the rules and procedures for writing and publishing scientific papers. After the community service activity, students were able to understand the material presented better. Another supporting factor in this activity was the high motivation of the participants to participate in the writing training.